Implementasi Media Bahasa dalam Pembelajaran MahÄrat Al-KalÄm Berdasarkan Fungsi Media Pembelajaran Menurut Kemp dan Dayton - Syafe'i, Isop (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
The purpose of this study was (1) to find out the language media in MahÄrat al-KalÄm learning (2) to find out the function of learning media according to Kemp and Dayton (3) to find out the language media in learning MahÄrat al-KalÄm Tsanawiyah Madrasah based on the function of instructional media according to Kemp and Dayton. This study uses a descriptive method with a qualitative approach, the researcher as a key instrument, data analysis is inductive, and the results of the study emphasize the meaning rather than the generalization of objects. Data collection techniques used were observation, in-depth interviews, and documentation. The findings of this study are: First, the language media that can be used by teachers in learning MahÄrat al-KalÄm are: Analogy, Antonyms, Synonyms, Give examples, Direct instruction, repeating words and sentences, and question and answer. Second, the function of learning media according to Kemp and Dayton, namely: motivating interests and actions, presenting information, and giving instructions. Third, there is a significant relationship between language media and the function of learning media according to Kemp and Dayton, so that it can be known the steps of learning by using language media in learning MahÄrat al-KalÄm.